2021
DOI: 10.1186/s12912-021-00581-8
|View full text |Cite
|
Sign up to set email alerts
|

Internationally trained nurses and host nurses’ perceptions of safety culture, work-life-balance, burnout, and job demand during workplace integration: a cross-sectional study

Abstract: Background The shortage of qualified nurses is a problem of growing concern in many countries. Recruitment of internationally trained nurses has been used to address this shortage, but successful integration in the workplace is complex and resource intensive. For effective recruitment and retention, it is important to identify why nurses migrate and if their expectations are met to ensure their successful integration and promote a satisfying work climate for the entire nursing team. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 48 publications
4
38
0
2
Order By: Relevance
“…This finding is congruent with Almalki et al 35 . and Roth et al 48 . findings, which had been attributed to the relationship between the nurses' clinical experience and the competence development assured by Almalki, 35 and that nursing competency was found to affect directly the QNC provided to patients.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This finding is congruent with Almalki et al 35 . and Roth et al 48 . findings, which had been attributed to the relationship between the nurses' clinical experience and the competence development assured by Almalki, 35 and that nursing competency was found to affect directly the QNC provided to patients.…”
Section: Discussionsupporting
confidence: 88%
“…This finding justified with that the more the nurses have practised and experienced, the more they will be competent. This finding is congruent with Almalki et al 35 and Roth et al 48 findings, which had been attributed to the relationship between the nurses' clinical experience and the competence development assured by Almalki, 35 and that nursing competency was found to affect directly the QNC provided to patients. Also, many studies 35,[47][48][49] have shown that more experienced nurses have more positive perceptions of the QNC.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Burnout may not be related to work-life balance significantly, but it affects the whole life of the employees by triggering negative emotions (Roth et al, 2021). The study of Roczniewska and Bakker (2021) showed that burnout affects the day-to-day behaviour regulation of nurses negatively.…”
Section: Introductionmentioning
confidence: 99%
“…Feeling exhausted, less success on performing the task related to the job and feeling detached from one's ‘self’ are some results of burnout. Burnout may not be related to work‐life balance significantly, but it affects the whole life of the employees by triggering negative emotions (Roth et al, 2021). The study of Roczniewska and Bakker (2021) showed that burnout affects the day‐to‐day behaviour regulation of nurses negatively.…”
Section: Introductionmentioning
confidence: 99%